Effect of Carboxymethyl chitosan-sodium alginate hydrogel loaded with Astragalus membranaceus-Panax notoginseng on wound healing in rats - Jing Li; Jing Li; Linai Li; Yue Yu; Ruixin Qin; Chaoyan Yu; Chen Chen; Youming Dong; Yadong Tan; Yunen Liu; Xuanli Liu (Frontiers in Pharmacology)
Skin wound healing is a complex physiological process that involves many different cell types and signaling molecules. In traditional Chinese medicine, A. membranaceus and Panax notoginseng are commonly used together for the treatment of wound injury for their significant efficacy. The application of new materials may make A. membranaceus-P. notoginseng (AP) play a better curative effect. In this study, we fabricated a Carboxymethyl chitosan-Sodium alginate hydrogel loaded with the extract of Astragalus membranaceus-P. notoginseng (APCS), which showed favorable stability, biocompatibility, and the ability to rapidly release drugs. Cell culture experiments demonstrated that the APCS hydrogel dramatically increased fibroblast proliferation, migration, and differentiation into myofibroblast. In vivo experiments of wound healing on SD rats showed that APCS hydrogels significantly accelerated skin wound healing, reduced inflammatory response, enhanced the formation of blood vessels, granulation tissues, and collagen fibers, and promoted re-epithelialization at the wound site. Increased expression of catalase, VEGF, and PGP9.5 of wound tissue indicated that APCS hydrogels inhibited oxidative stress and promoted vascular and neuronal regeneration. In summary, the APCS hydrogel displayed great potential as a dressing for achieving satisfactory healing of full-thickness wounds.